Pengaruh Jumlah Penduduk, Tingkat Pengangguran dan Indeks Pembangunan Manusia Berdasarkan Nilai Maqashid Syariah Terhadap Kemiskinan di Provinsi Jambi Tahun 2019–2023 - Mutiarawani, Vira; Mubyarto, Novi; Anggraini, Dessy; Anggraeni , Lidya (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2025)
Poverty remains a pressing and complex social challenge that requires diligent attention and strategic intervention from both regional and central governments, as its presence can trigger a cascade of societal problems. Numerous interrelated factors contribute to poverty, including population growth, the prevalence of unemployment, and the Human Development Index (HDI), which serves as a comprehensive indicator of a community’s overall well-being, education, and standard of living. This study seeks to examine and illuminate the intricate ways in which population size, unemployment rate, and HDI collectively shape and influence poverty levels in Jambi Province. Employing a rigorous quantitative research design, the study draws upon secondary data meticulously compiled by the Central Statistics Agency (BPS) for the period spanning 2019 to 2023. To uncover the nuanced dynamics and causal relationships among these socioeconomic variables, the analysis is conducted using panel data regression, specifically through the Fixed Effect Model (FEM), offering valuable insights into the multifaceted nature of poverty in the region.